Analysis of User Acceptance of E-Learning at SMP NEGERI 10 PENAJAM PASER UTARA Using the UTAUT 2 Model - Pratama, Maulana Adhie; Hadisaputro, Elvin Leander (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The rapid development of information and communication technology has encouraged the use of electronic media in education, giving rise to a new paradigm in learning through e-learning. E-learning provides benefits such as access to various learning resources and improving the quality of student-centered learning. This research analyzes the factors that influence student satisfaction in using e-learning by adopting the UTAUT (Unified Theory of Acceptance and Use of Technology) model and evaluates their intention to continue using this technology. The research was conducted at SMP Negeri 10 Penajam Paser Utara using a Moodle-based Learning Management System (LMS). Data was collected through an online survey with Google Forms from a sample of active students using e-learning in 2023. The results of the analysis show that the research model has good validity and reliability. Research findings indicate that habitual factors have a significant influence on usage intentions, which in turn influence usage behavior. Performance expectations also influence the intention to use e-learning.